2020
DOI: 10.21037/atm-19-4552
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vitamin C alleviates pancreatic injury via the NRF2/NQO1/HO-1 pathway in a rat model of severe acute pancreatitis

Abstract: Background: Oxidative stress plays a pivotal role in the progress of severe acute pancreatitis (SAP).Vitamin C (VC) is the most important antioxidant in plasma. However, the effects of an intravenous administration of high-dose VC and the mechanisms by which it exerts its antioxidant function in an experimental model of SAP have not been determined.Methods: Sodium taurocholate was used to induce rat pancreatic injury and AR42J cells injury. After the establishment of SAP model, SAP rat and injured AR42J cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In a rat model of severe acute pancreatitis and an in vitro model of taurocholate-induced injury in AR42J rat pancreatic acinar cells, vitamin C has been shown to attenuate pancreatic cell injury likely via activating the Nrf2/NQO1/HO-1 pathway [46]. Notably, the protective effects of vitamin C on taurocholate-induced AR42J cell injury was attenuated by Nrf2 knockdown [46], suggesting a causal role for Nrf2 signaling in mediating vitamin C cytoprotection. Presently, how vitamin C activates Nrf2 signaling remains unclear though an early study suggested a possible involvement of phosphoinositide 3-kinase [47].…”
Section: Activating Nrf2 Signalingmentioning
confidence: 98%
See 1 more Smart Citation
“…In a rat model of severe acute pancreatitis and an in vitro model of taurocholate-induced injury in AR42J rat pancreatic acinar cells, vitamin C has been shown to attenuate pancreatic cell injury likely via activating the Nrf2/NQO1/HO-1 pathway [46]. Notably, the protective effects of vitamin C on taurocholate-induced AR42J cell injury was attenuated by Nrf2 knockdown [46], suggesting a causal role for Nrf2 signaling in mediating vitamin C cytoprotection. Presently, how vitamin C activates Nrf2 signaling remains unclear though an early study suggested a possible involvement of phosphoinositide 3-kinase [47].…”
Section: Activating Nrf2 Signalingmentioning
confidence: 98%
“…Nrf2 is a major regulator of cellular antioxidative and other cytoprotective genes [45]. In a rat model of severe acute pancreatitis and an in vitro model of taurocholate-induced injury in AR42J rat pancreatic acinar cells, vitamin C has been shown to attenuate pancreatic cell injury likely via activating the Nrf2/NQO1/HO-1 pathway [46]. Notably, the protective effects of vitamin C on taurocholate-induced AR42J cell injury was attenuated by Nrf2 knockdown [46], suggesting a causal role for Nrf2 signaling in mediating vitamin C cytoprotection.…”
Section: Activating Nrf2 Signalingmentioning
confidence: 99%
“…Four studies that did not report main outcomes of interest were excluded (32)(33)(34)(35), and two studies reported overlapping data, so one of them was excluded (36). Finally, four studies were included in the metaanalysis for clinical trials (37)(38)(39)(40) and nine articles (41)(42)(43)(44)(45)(46)(47)(48)(49) in the meta-analysis for preclinical studies (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The cellular events important to the pathogenesis of AP include pathological calcium signaling (10)(11)(12), premature trypsinogen activation within macrophages and acinar cells (13)(14)(15), mitochondrial dysfunction (16,17), endoplasmic reticulum (ER) stress (18,19), impaired autophagy, and impaired unfolded protein response (UPR) (17). These events are caused by usual acinar cell toxins, such as nicotine, alcohol, and bile acids.…”
Section: Incidencementioning
confidence: 99%